If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 15x + -5 Reorder the terms: y = -5 + 15x Solving y = -5 + 15x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -5 + 15x
| 4(1.5+0.25y)-y=6 | | -2(5)q+(-72)(-q)= | | 2x-11x+28=0 | | 2(3+-3y)-y=-8 | | 6n-20=-26+9n | | 3y-24=-39+8y | | 12x^3+8x^2+27x+18=0 | | .5-2x=x | | 14x^2+19x=3 | | 28=2-5x | | ln(x-2)+(lnx)=0 | | 16+7y+-8= | | -2q^2+12q=0 | | a=29.5+-1.5625b | | 2ln(x)=ln(25) | | -12x^3-21x^2=-6x | | 32a+50b=944 | | -23x+7y=-3 | | 3.4e=3.74 | | 13x+72=-23 | | 4x*4= | | 2x^2-3x+4=3 | | 2a+3b=58.6 | | 1ax(2b+3c)= | | 30a+50b=944 | | 0=x^2+48x+398 | | 8(x+6)-35= | | 2x-3x+4=3 | | 2a+3b=58 | | 4log(2x-3)=14 | | (ab+a+b+6)+(3ab-b+c-6)= | | 4x^2+2x+15=0 |